Genome-wide Association and Meta-analysis of Age at Onset in Parkinson Disease: Evidence From the COURAGE-PD Consortium. (16th August 2022) - Grover, Sandeep; Kumar Sreelatha, Ashwin Ashok; Pihlstrom, Lasse; Domenighetti, Cloé; Schulte, Claudia; Sugier, Pierre-Emmanuel; Radivojkov-Blagojevic, Milena; Lichtner, Peter; Mohamed, Océane; Portugal, Berta; Landoulsi, Zied; May, Patrick; et al.
Abstract : Background and Objectives: Considerable heterogeneity exists in the literature concerning genetic determinants of the age at onset (AAO) of Parkinson disease (PD), which could be attributed to a lack of well-powered replication cohorts. The previous largest genome-wide association studies (GWAS) identified SNCA and TMEM175 loci on chromosome (Chr) 4 with a significant influence on the AAO of PD; these have not been independently replicated. This study aims to conduct a meta-analysis of GWAS of PD AAO and validate previously observed findings in worldwide populations. Methods: A meta-analysis was performed on PD AAO GWAS of 30 populations of predominantly European ancestry from the Comprehensive Unbiased Risk Factor Assessment for Genetics and Environment in Parkinson's Disease (COURAGE-PD) Consortium. This was followed by combining our study with the largest publicly available European ancestry dataset compiled by the International Parkinson Disease Genomics Consortium (IPDGC). Results: The COURAGE-PD Consortium included a cohort of 8, 535 patients with PD (91.9%: Europeans and 9.1%: East Asians). The average AAO in the COURAGE-PD dataset was 58.9 years (SD = 11.6), with an underrepresentation of females (40.2%). The heritability estimate for AAO in COURAGE-PD was 0.083 (SE = 0.057). None of the loci reached genome-wide significance ( p < 5 × 10 −8 ). Nevertheless, the COURAGE-PD dataset confirmed the role of the previously published TMEM175 variant as a genetic determinant of the AAO of PD with Bonferroni-corrected nominal levels of significance ( p < 0.025): (rs34311866: β(SE)COURAGE = 0.477(0.203), p COURAGE = 0.0185). The subsequent meta-analysis of COURAGE-PD and IPDGC datasets (Ntotal = 25, 950) led to the identification of 2 genome-wide significant association signals on Chr 4, including the previously reported SNCA locus (rs983361: β(SE)COURAGE+IPDGC = 0.720(0.122), p COURAGE+IPDGC = 3.13 × 10 −9 ) and a novel BST1 locus (rs4698412: β(SE)COURAGE+IPDGC = −0.526(0.096), p COURAGE+IPDGC = 4.41 × 10 −8 ). Discussion: Our study further refines the genetic architecture of Chr 4 underlying the AAO of the PD phenotype through the identification of BST1 as a novel AAO PD locus. These findings open a new direction for the development of treatments to delay the onset of PD.